10.2174/0250688202666210402094638 - Manjappa Mahadevappa; Prashanth Kulkarni; KS Poornima; Rajendra Prasad (New Emirates Medical Journal, 2021)
Background: Lactic acidosis of any etiology is associated with poor prognosis and often fatal. The survival in lactic acidosis depends on the ability to identify and remove the cause and managing organ perfusion. Nucleoside Reverse Transcriptase Inhibitors (NRTIs), which are used widely in the treatment of Human Immune Deficiency Virus (HIV) infection, are known to cause life-threatening Type B lactic acidosis. Case Presentation: Severe lactic acidosis can cause organ failure, especially in respiratory and cardiovascular systems. However, the role of acute lactic acidosis in these organ failures is mostly suggested by experimental studies in animals or in vitro, as few clinical studies in humans are available. Acidosis elevates pulmonary vascular resistance, giving rise to pulmonary hypertension and peripheral vasodilation with an associated fall in blood pressure and systemic hypotension. Although lactic acidosis presenting as abdominal pain, vomiting, and pancreatitis have been reported in persons receiving antiretroviral therapy, the presentation as acute right heart failure has rarely been documented in the literature. We report a case of severe metabolic and lactic acidosis in a patient receiving stavudine and lamivudine, with a rare and atypical presentation as acute right heart failure and severe pulmonary hypertension. Conclusion: This case emphasizes the need to consider lactic acidosis as a potential cause in patients presenting with acute unexplained right heart failure and severe pulmonary hypertension.